Translation Techniques in Literary Poetry Texts: A Systematic Literature Review - Mauladiana, Istifani; Juniardi, Yudi (Indonesian Journal of Teaching and Teacher Education, 2024)
Translating poetry presents a distinct challenge as it requires preserving the emotional depth, such as mood and tone of the source text while maintaining structural elements; rhyme, meter, and line count. This balance demands creativity and precision from translators to ensure equivalence in the target language. This study employs a Systematic Literature Review (SLR) method to explore the techniques used intranslating literary poetry, focusing on journal articles published between 2017 and 2024. Insights from nine key publications were consolidated, highlighting essential translation techniques and their application in various contexts. The result showed that there are sixteen translation techniques found based on Molina and Albir (2002), along with ten other strategies that cater to the evolving demands of poetry translation, offering guidance for translators to adapt their approaches based on the purpose and artistic requirements of the work. These findings contribute to a deeper understanding of the strategies used to navigate the intricate process of poetry translation.